Pembinaan Laporan Keuangan Dengan Memanfaatkan Software Application - Sunarsan Sitohang; Very Karnadi; Cosmas Eko Suharyanto (ASOSIASI IDEBAHASA KEPRI, 2021)
The convenience that is currently obtained in doing work is the role of rapidly developing technology and the need to complete a job quickly. It is undeniable that there are still many people who are very reluctant to technology use. This reluctance can be caused by lack of will learning or inadequate facilities and the absence of motivating or construction. Guidance on the use of application software aims to make Church administrators Bethel Indonesia (GBI) Rawa Indah RT.03 RW.12 No.10 Kibing Batu Aji can understand how to use application software, namely Microsoft office excel to assist in how to use application software for good church activities in the form of making good financial reports, good invitation letters and others etc. The method of service carried out is by providing material about the use of application software in the form of tutorials that are made simply with easy-to-understand steps and direct practice and accompanied by a coaching team in addition to that will be given training to evaluate the level of understanding of the coaching participants. Therefore, application software development it will be indispensable for church administrators who are interested in studying it. The main target of this development is to create a society that can implement technology, especially application software to make it easier to work on work, especially in financial reporting by utilizing software application and understand how to use the application software. Results dedication shows that the targets set can be achieved, namely the management GBI Rawa Indah church can apply Microsoft Excel to make reports finance.